Comparison of Deferasirox and Desferrioxamine in Term of Mean Serum Ferritin Levels in Patients of β-Thalassemia Major with Iron Overload: Effect of Deferasirox and Desferrioxamine in β-Thalassemia Major - Iram, Khadeeja; Ali, Zulfiqar; Aamer, Fauzia; Shiekh, Aslam; Hassan, Maria (Pakistan Journal of Health Sciences, 2024)
Iron chelation treatments as adjuvant therapy can reduce iron stores to minimize the related morbidity and mortality in patients with thalassemia major. Objective: To compare Deferasirox (DFX) and Desferrioxamine (DFO) in terms of mean serum ferritin levels in patients of β-thalassemia major having Iron overload. Methods: This randomized controlled trial was conducted at the Thalassemia Center of Hematology Department, “The Children’s Hospital and The Institute of Child Health”, Multan, Pakistan from January 2023 to September 2023. After randomization, children in DFO group were given DFO in a dose of 50mg/kg, through subcutaneous route by infusion pump five days a week. Children in DFX group were given DFX in a dose of 30mg/kg, orally in tablet form once daily. Baseline serum ferritin levels were measured and the change in mean serum ferritin level for each group was calculated and compared for both groups after 6-months of treatment. Results: In a total of 142 children, 87 (61.3%) children were male. The mean age was 7.08 ± 2.41 years. The mean number of blood transfusions at the time of enrollment were 13.4 ± 4.2. After 6 months of treatment in DFO versus DFX groups, the net change in mean serum ferritin levels from baseline to post-treatment was 947.2 ± 454.0 µg/L for DFO and 1053.5 ± 389.8 µg/L for DFX, with no statistically significant difference between the groups (p=0.1367). Conclusions: Once-daily oral deferasirox has good compliance, acceptable tolerability and appears to have similar efficacy to desferrioxamine in reducing iron burden of transfused patients with beta thalassemia major.